2016
DOI: 10.3389/fpsyg.2016.01413
|View full text |Cite
|
Sign up to set email alerts
|

Vowels and Consonants in the Brain: Evidence from Magnetoencephalographic Studies on the N1m in Normal-Hearing Listeners

Abstract: Speech sound perception is one of the most fascinating tasks performed by the human brain. It involves a mapping from continuous acoustic waveforms onto the discrete phonological units computed to store words in the mental lexicon. In this article, we review the magnetoencephalographic studies that have explored the timing and morphology of the N1m component to investigate how vowels and consonants are computed and represented within the auditory cortex. The neurons that are involved in the N1m act to construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 172 publications
1
7
0
Order By: Relevance
“…Thus, our results generalize this effect to the spectral content of complex tones in more realistic and complex auditory sequences. Moreover, speech research showing modulations of the N1m component by the acoustic properties of phonemes provides further support to our proposal (Manca & Grimaldi, 2016;Shestakova, Brattico, Soloviev, Klucharev, & Huotilainen, 2004). On the same line, in a previous EEG study reporting an effect similar to the one found here, manipulations of surprise were also confounded with interval size, which is consistent with our data (Koelsch & Jentschke, 2010).…”
Section: Interval Size and Sensory Adaptation Better Explain N1m Respsupporting
confidence: 83%
“…Thus, our results generalize this effect to the spectral content of complex tones in more realistic and complex auditory sequences. Moreover, speech research showing modulations of the N1m component by the acoustic properties of phonemes provides further support to our proposal (Manca & Grimaldi, 2016;Shestakova, Brattico, Soloviev, Klucharev, & Huotilainen, 2004). On the same line, in a previous EEG study reporting an effect similar to the one found here, manipulations of surprise were also confounded with interval size, which is consistent with our data (Koelsch & Jentschke, 2010).…”
Section: Interval Size and Sensory Adaptation Better Explain N1m Respsupporting
confidence: 83%
“…With regard to vowels specifically, MEG studies have shown differences between vowels in equivalent current dipole localization of the N1m component (Diesch and Luce 1997; Mäkelä et al, 2003; Obleser et al, 2003, 2004; Shestakova et al, 2004; Scharinger et al, 2011, 2012). These studies have shown that vowel pairs that are more dissimilar in F 1 / F 2 space, or that differ by more distinctive features, generally show larger Euclidean distances between their dipole locations (Manca and Grimaldi, 2016). However the specific orientations of differences in dipole locations in relation to formant frequencies have been inconsistent across studies (Manca and Grimaldi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that vowel pairs that are more dissimilar in F 1 / F 2 space, or that differ by more distinctive features, generally show larger Euclidean distances between their dipole locations (Manca and Grimaldi, 2016). However the specific orientations of differences in dipole locations in relation to formant frequencies have been inconsistent across studies (Manca and Grimaldi, 2016). This may reflect the fact that single dipoles are used to model complex patterns of activity that involve the representation of multiple formants on multiple tonotopic gradients, which may be oriented in idiosyncratic ways according to individual anatomy of Heschl’s gyrus and other tonotopically organized regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They directly correspond to F1 and F2 values, which, in turn, find their straight correlates in regions and types of brain activity. The rounding feature appears more complex, as it requires higher-level information processing and is acoustically less reliable and perceived with significant help from the visual channel (Traunmüller & Öhrström, 2007;Eulitz & Obleser, 2007;Vatakis et al, 2012;Manca & Grimaldi, 2016). One might thus suggest that u is less perceptually robust and salient than i and, therefore, more prompt for reduction, especially in languages with fronting vowel harmony.…”
Section: Synchronic Variation and Sound Changementioning
confidence: 99%